1991
DOI: 10.2172/10176893
|View full text |Cite
|
Sign up to set email alerts
|

Sample application of sensitivity/uncertainty analysis techniques to a groundwater transport problem. National Low-Level Waste Management Program

Abstract: The primary objective of this document is to provide sample applications o f selected sensitivity and uncertainty analysis techniques within the context of the radiological performance assessment process. These appl ications were drawn from the companion document Guide7 ines f o r S e n s i t i v i t y and Uncertainty AnaTIyses o f Low-Leve7 Radioactive Waste Performance Assessment Computer Codes (S. Maheras and M, Kotecki , DOE/LLW-100, 1990). Three techniques are illustrated in this document: one-factor-at-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1992
1992
1994
1994

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The PORFLO peak flux exceeds the GWSCREEN peak flux. A similar observation of contaminantconcentrationwas made by Seitz et al (1991) lt was shown that for Peclet numbers less than about 50, the peak concentration,and consequently,the peak mass flux, increased when the ratio of contaminant half-life to contaminant transit time was decreased to less than 0.1 (Figure 12). The Peclet number for this simulationwas Pe = 9.Im+ 0.5 m = 18 One method to assure conservatismis to make sure the half-life/transittime ratio be limited to a minimum value of 0.1.…”
Section: Contaminant Andsite Specific Datafilesupporting
confidence: 77%
See 2 more Smart Citations
“…The PORFLO peak flux exceeds the GWSCREEN peak flux. A similar observation of contaminantconcentrationwas made by Seitz et al (1991) lt was shown that for Peclet numbers less than about 50, the peak concentration,and consequently,the peak mass flux, increased when the ratio of contaminant half-life to contaminant transit time was decreased to less than 0.1 (Figure 12). The Peclet number for this simulationwas Pe = 9.Im+ 0.5 m = 18 One method to assure conservatismis to make sure the half-life/transittime ratio be limited to a minimum value of 0.1.…”
Section: Contaminant Andsite Specific Datafilesupporting
confidence: 77%
“…The cumulative flux for both models is the same as time approaches infinity. For contaminantswith short half-lives 2, under conditionswhere the dispersivity is large, the peak flux may actually be larger using a dispersion model as compared to a plug flow model (Seitz et al, 1991) because the contaminant arrives at the receptor sooner resulting in reduced decay time. Dispersivity in the unsaturated zone would not be readily available during the initial groundwater assessmentprocess and since other conservativeassumptions, such as increasingthe percolation rate and reducing the unsaturated zone thickness, may be assumed to compensatefor the effect of dispersion on short half-lived contaminants, dispersionwas not consideredand the simpler plug-flow model IThe contaminant half-life is greater than 1/10 the contaminant transit time in the unsaturated zone was used.…”
Section: 3 Unsaturated Zone Model Qmentioning
confidence: 99%
See 1 more Smart Citation
“…For contaminants with short half-lives relative to their residence time in the unsaturated zone, the plug flow assumption may not be conservative since the contaminant will arrive sooner (lower residence time in the unsaturated zone) when dispersion is considered, therefore allowing less time to decay. This observation was noted by Seitz et al (1991) and may become a significant factor when the unsaturated transit time [see Equation 21] is greater than 10 times the half-life of the contaminant. Dispersion coefficients in the unsaturated zone would not be readily available during the initial groundwater assessment process.…”
Section: Unsaturated Zone Modelmentioning
confidence: 90%
“…Sensitlvlty/uncer-prepared as part of the Concrete Barriers Project. tainty analysis has been recognized as a critical New information about approaches not addressed part of a PA (Campbell et al 1993; in the previous documents and papers is also 1993; Seitz et al 1991;Seitz et al 1992a).…”
Section: Code the Individual Models All Run In Relativelymentioning
confidence: 99%